THE IMPORTANCE OF AN AUTOMATED CHECKING SYSTEM AND ITS APPLICATION IN EDUCATIONAL INSTITUTIONS - Abdukarimov Sirojiddin Sayfiddin Ugli (International Scientific and Current Research Conferences, 2023)
This article explores the significance and application of automated checking systems in the realm of educational institutions, particularly focusing on their utility in programming competitions and academic assessments. With the increasing prevalence of software solutions, there is a pressing need for efficient and fair testing methods. The paper discusses the current landscape of automated testing, highlighting the lack of literature on automated task testing systems despite their successful implementation in various countries.